Standard English and standards in English in a changing world : a case study - Irish Standard English - White, Goodith (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2005)
This study investigates the question ‘Does such a phenomenon as Irish Standard English exist, and if it does, what are some of the characteristics of its forms and use?’ The research question is investigated in three ways. A distinction is drawn between ‘language standards’, which are defined as the rules which prescribe what is considered to be standard in a language, and which encompasses both attitudes towards the standard variety and prescriptive statements about the linguistic norms to which it should conform, and ‘standard language’ which is concerned with the actual linguistic forms which standard language users employ. It is argued that all three approaches, that is, attitudes, prescriptions and instances of actual standard language use have something to contribute to the construction of a case for the existence of Irish Standard English, although the third approach may have the most to offer.
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin